Nematode communities in irrigated and rainfed rice fields in Sukabumi Regency, West Java - Abdul Munif; Della Sitanggang; Fatimatuzzahroh Fatimatuzzahroh; Muhammad Mirsodi; Amelia Kusumawardhani; Nurul Fitria Indiyanti (Universitas Trunojoyo Madura, 2025)
Parasitic nematodes are among the most important constraints in rice cultivation, yet information on their community structure in Sukabumi, West Java, remains limited. Understanding nematode ecology in this region is essential to develop sustainable management practices, particularly given the dominance of rice monoculture and the contrasting water management systems between irrigated and rainfed fields. This study aimed to characterize nematode diversity and community composition in both ecosystems and to assess their potential implications for agroecosystem health. Soil and root samples were collected from irrigated and rainfed rice fields, and nematodes were extracted using standard methods before identification to the genus level. Ecological indices were calculated to evaluate community structure. The results revealed relatively low diversity (H’ = 0.71–0.94), low evenness (E = 0.52–0.61), and high dominance (C = 0.42–0.58). Irrigated fields supported a greater number of genera but were strongly dominated by Meloidogyne, reflecting the favorable conditions of constant flooding for root-knot nematodes. In contrast, rainfed fields contained fewer taxa but showed marked dominance of Criconemella, a genus more tolerant to soil compaction and moisture fluctuations. These differences demonstrate that intensification and water regimes significantly influence nematode assemblages, leading to distinct ecological patterns and potential risks for rice production. Nematode communities in Sukabumi are characterized by low diversity and high dominance of parasitic genera, which may undermine soil health and long-term productivity. Nematodes found in both irrigated and rainfed fields exhibited low diversity, low evenness, and high dominance. The nematodes identified in irrigated rice fields included genus Helicotylenchus, Rhabditis, Meloidogyne, Hirschmanniella, Tylenchorhynchus, Pratylenchus, and Aphelenchoides. Nematodes found in rainfed rice fields included Meloidogyne, Hirschmanniella, and Criconemella. Meloidogyne spp. was one of the dominant nematodes found in both root and soil samples across various rice cultivation types and locations. These findings highlight the urgent need for integrated nematode management strategies, including resistant varieties, organic amendments, crop rotation, and biological control agents, to sustain rice agroecosystems and secure food production in West Java